2011
DOI: 10.4209/aaqr.2011.08.0119
|View full text |Cite
|
Sign up to set email alerts
|

Particle-bound PAHs and Particle-extract-induced Cytotoxicity of Emission from a Diesel-generator Fuelled with Soy-biodiesel

Abstract: This study investigates the size distribution of nano/ultrafine particle-bound PAHs (polycyclic aromatic hydrocarbons) and the PAH-associated carcinogenic potency/cytotoxicity of the exhaust from a generator that is fuelled with D100 (pure petroleum diesel) and S20 (v/v = 20% soy-biodiesel/80% D100) and operated at stable energy output loads (0 and 3 kW). A micro-orifice uniform deposit impactor (MOUDI) and a Nano-MOUDI (with aerodynamic diameters of 0.01-18 μm) were used to collect PM samples. The cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Atmospheric particles with diameters of under 10 μm can enter human lungs by respiration, causing or worsening respiratory and cardiovascular diseases (Sardar et al, 2005;Brook, 2007;Franck et al, 2011). Additionally, studies of the in-vitro testing of atmospheric particles have shown that the components of PMs (such as water-soluble ions and polycyclic aromatic hydrocarbons) may be toxic to cells Lin et al, 2008;Tsai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric particles with diameters of under 10 μm can enter human lungs by respiration, causing or worsening respiratory and cardiovascular diseases (Sardar et al, 2005;Brook, 2007;Franck et al, 2011). Additionally, studies of the in-vitro testing of atmospheric particles have shown that the components of PMs (such as water-soluble ions and polycyclic aromatic hydrocarbons) may be toxic to cells Lin et al, 2008;Tsai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The residues thus obtained were then resuspended in dimethyl sulfoxide (DMSO) and stored in a freezer at -80°C until the cytotoxicity assay was performed using porcine human male monocytic cell strain (U937) as part of an in vitro screening system. Further details of the preparation programs can be found in our earlier works (Tsai et al, 2011b(Tsai et al, , 2012.…”
Section: Preparation Of Exhaust Samples Extractsmentioning
confidence: 99%
“…However, the contribution of natural sources to PAH emission into atmospheric environments may be insignificant (Wild and Jones, 1995). These pollutants are present at ambient temperature in the atmosphere, as the gas-phase or adsorbed on atmospheric particulates, depending upon their chemical and physical properties (Ravindra et al, 2008;Tsai et al, 2011;Wang et al, 2011). Among the hundreds of PAH compounds found in the environment, 16 are classified as priority pollutants by the USEPA (2003).…”
Section: Introductionmentioning
confidence: 99%